Discrimination between Functional and Non-functional Cellular Gag Complexes involved in HIV-1 Assembly. Issue 8 (16th April 2021) - Deng, Yisong; Hammond, John A.; Pauszek, Raymond; Ozog, Stosh; Chai, Ilean; Rabuck-Gibbons, Jessica; Lamichhane, Rajan; Henderson, Scott C.; Millar, David P.; Torbett, Bruce E.; Williamson, James R.
Graphical abstract: Highlights: HIV-1 Gag-containing complexes (GCCs) are formed in all cells Gag is expressed in. These complexes have been proposed to be intermediates in HIV-1 assembly. Here we show that most of these complexes are not on-pathway intermediates. Most GCCs are monomer Gags bound to ribosomes and precede virus formation. This may be a mechanism to inhibit premature RNA-driven Gag oligomerization in vivo . Abstract: HIV-1 Gag and Gag-Pol are responsible for viral assembly and maturation and represent a major paradigm for enveloped virus assembly. Numerous intracellular Gag-containing complexes (GCCs) have been identified in cellular lysates using sucrose gradient ultracentrifugation. While these complexes are universally present in Gag-expressing cells, their roles in virus assembly are not well understood. Here we demonstrate that most GCC species are predominantly comprised of monomeric or dimeric Gag molecules bound to ribosomal complexes, and as such, are not on-pathway intermediates in HIV assembly. Rather, these GCCs represent a population of Gag that is not yet functionally committed for incorporation into a viable virion precursor. We hypothesize that these complexes act as a reservoir of monomeric Gag that can incorporate into assembling viruses, and serve to mitigate non-specific intracellular Gag oligomerization. We have identified a subset of large GCC complexes, comprising more than 20 Gag molecules, that may be equivalent to membrane-associated puncta previously shown to be bona fide assembling-virus intermediates. This work provides a clear rationale for the existence of diverse GCCs, and serves as the foundation for characterizing on-pathway intermediates early in virus assembly.